The Effect of First Aid Training Using the Demonstration Method on the Management of Coronary Heart Disease in Fishermen (In Bulumeduro Village, Bancar District, Tuban Regency) - Ferianto, Kusno; Fitriana, Nur Aida (LLDIKTI Wilayah 1, 2024)
The Ability to Manage Coronary Heart Disease Among Fishermen in Indonesia is Still Low. This indicates that efforts to improve the ability to manage Coronary Heart Disease among fishermen must be increased. First Aid Training using the Demonstration Method will help fishermen better understand the management of Coronary Heart Disease. This study aims to determine the effect of First Aid Training with the Demonstration Method on fishermen in Bulumeduro Village, Bancar District, Tuban Regency. The research design used in this study was a pre-experimental design with a one-group pre-post test approach, using a cross-sectional time frame. The sample consisted of 35 participants, selected through simple random sampling, resulting in 32 respondents. The independent variable was First Aid Training, and the dependent variable was the management of Coronary Heart Disease, which was measured using the Wilcoxon test. Data analysis in this study was conducted using the Wilcoxon test with a significance level of ? = 0.05, and the data were processed using SPSS version 25.0 for Windows. The results showed an Asymp. Sig. value of 0.000. Therefore, with p = 0.000 < 0.05, H1 was accepted, indicating that there is an effect of First Aid Training using the Demonstration Method on the management of Coronary Heart Disease among fishermen in Bulumeduro Village, Bancar District, Tuban Regency.